Prevalence of dry eye disease in rheumatoid arthritis patients and its correlation with duration of rheumatoid arthritis - Priyanshi Ashishbhai Gandhi; Arun Kumar Samar; Nitish Kathuria; Avinash Mishra; Harbeer Singh Chhabra (The Pan-American Journal of Ophthalmology)
Background: Dry eye is a condition of the tear film and ocular surface that causes discomfort, visual disturbance, and tear film instability. The subjective symptoms in dry eye disease (DED) are often nonspecific. More or less common are conjunctival redness and damage to the ocular surface with punctate epithelial erosions. Rheumatoid arthritis (RA) is a systemic autoimmune disease with approximately 25% of patients having ocular manifestations. Methodology: A prospective observational study was carried out in the ophthalmology outpatient department of a tertiary care center. There were 200 RA patients enrolled. Dry eye workup was done using various tests and the Ocular Surface Disease Index questionnaire. RA patients were divided on the basis of duration of illness into two groups. The results of dry eye tests were compared between these two groups. Results: Out of 200 RA patients, 89% were females. The overall prevalence of dry eye was 52.5% according to Schirmer’s test without anesthesia. There were 112 patients who were suffering from RA for <5 years and another group of 88 patients who were suffering for ≥5 years. Schirmer’s test and corneal fluorescein staining suggested that the patients with longer duration of RA are more prone to DED. Conclusion: The prevalence of dry eyes in patients with RA is high. Chronic ocular surface changes were observed with the longer duration of RA disease activity which affects the quality of life in such patients.